Melestarikan Budaya Lokal di Tengah Arus Globalisasi Digital - Kartika Darwil; Faraz Ramli; Fitra Nawaz (Journal of Community Development and Empowerment, 2026)
The current of digital globalization has a significant impact on societal patterns, including the existence of local cultures that are increasingly marginalized by global culture. This community service project aims to preserve local culture through the adaptive and sustainable use of digital technology. The activities were conducted within a local community using a participatory approach, involving traditional leaders, youth, and cultural practitioners. Methods used included socialization on the importance of cultural preservation, digital literacy training, and mentoring in the creation of local cultural content for social media and digital platforms. The results indicate an increase in public awareness regarding local cultural values and an improvement in participants' ability to document and promote regional culture through digital media. Furthermore, the younger generation demonstrated high enthusiasm for packaging local culture creatively and relevantly to modern times. This program also encouraged the creation of digital spaces as a means of cultural education and promotion that is widely accessible. Thus, the utilization of digital technology is not only a challenge but also a strategic opportunity to maintain the sustainability of local culture amidst rapid globalization. This service activity is expected to serve as a model for strengthening local cultural identity that can adapt to technological developments and provide a real contribution to the preservation of the nation's cultural heritage.